THE MOTIVATIONAL EFFICACY OF SELF-REGULATED ICT RESOURCES ON INTEREST IN BIOLOGY AMONG HIGH, MEDIUM, AND LOW ACHIEVING SECONDARY SCHOOL STUDENTS - Dada, Fehintoluwa E.; Paramole, Oyeronke C.; Fakokunde, Jubril; Adewale, Peter; Yusuf, Florence A.; Abimbola, Isaac O. (FUDMA JOURNAL OF SCIENCES, 2024)
This study examined the impact of technological software on learning from an interactive hypermedia. It explores participants’ learning interest and engagement, analyzing variations based on their score levels. The mixed method study adopted a pretest, posttest, quasi-experimental design using 3x2x3 factorial matrix, a Semi-Structured interview guide, and a Students’ interest inventory, entitled Questionnaire on the effect of ICT Resources on the Interest of Students in Biology (QEIISB) utilized to elicit responses on students’ interest. Post-hoc analysis was used to determine the direction of difference and findings revealed were discussed in the context of perfect understanding across achievement levels, because participants showed better interest and engagement more in the group of medium Scorers. The medium score level students showed significant interest and benefitted most from the software. By evaluating the efficiency of Information and Communication Technological (ICT) tools, influence students with varying performance or achievement levels, the study aims to provide insights into the effective these resources influence achievement and foster better interest in teaching and learning.